2012
DOI: 10.1093/cid/cir928
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diseases, Chromosomal Abnormalities, and Congenital Malformations as Risk Factors for Respiratory Syncytial Virus Hospitalization: A Population-Based Cohort Study

Abstract: Chronic disease per se is an important risk factor for RSV hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
127
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 39 publications
16
127
2
1
Order By: Relevance
“…First, the groups were assembled in 2 different countries over different time frames with varying baseline characteristics and environmental risk factors that could influence the severity of RSV infection and hospitalization in the respective DS populations. [39][40][41][42] However, studies on children with DS from the Netherlands, 3 Denmark, 2 Israel, 5 and the United States 1,6 have reported similar RSV hospitalization rates, as previously reported in this untreated cohort. 3 Moreover, the greater prevalence of risk factors in the treated group suggests possible underestimation of the treatment effect of RSV prophylaxis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…First, the groups were assembled in 2 different countries over different time frames with varying baseline characteristics and environmental risk factors that could influence the severity of RSV infection and hospitalization in the respective DS populations. [39][40][41][42] However, studies on children with DS from the Netherlands, 3 Denmark, 2 Israel, 5 and the United States 1,6 have reported similar RSV hospitalization rates, as previously reported in this untreated cohort. 3 Moreover, the greater prevalence of risk factors in the treated group suggests possible underestimation of the treatment effect of RSV prophylaxis.…”
Section: Discussionsupporting
confidence: 80%
“…Down syndrome (DS) is an independent risk factor for respiratory illness and severe respiratory syncytial virus (RSV)-related infection and hospitalization in children. [1][2][3][4][5][6][7][8] The combined attributes of a compromised innate and adaptive immune system in early infancy [9][10][11][12][13] with anatomic [14][15][16] and physiologic aberrations such as gastroesophageal reflux disease, 17 obstructive sleep apnea, 18 and hemodynamically significant heart disease 4,19 all lead to significant morbidity and mortality in DS during the first 2 years of life. [20][21][22] Palivizumab, a humanized monoclonal antibody, has been proven safe and efficacious against RSV in randomized, placebo-controlled studies involving preterm infants #35 weeks' gestational age during their first RSV season and children aged ,2 years with severe chronic lung disease (CLD) and hemodynamically significant cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,22 The reported proportions of children with chronic conditions hospitalized with RSV have ranged widely, possibly reflecting the variable underlying populations and study designs. 6,15,17,24 Stockman et al 6 recently found that 12% of RSV-hospitalized children ,12 months old and 2.4% of those 12 to 23 months old had heart disease, chronic neonatal respiratory distress, or prematurity, as determined by RSV ICD-9-CMcoded discharge diagnoses. In comparison, we found that 21% of RSV-hospitalized children ,12 months old and 53% of children 12 to 23 months old had chronic conditions, as determined by medical chart review.…”
Section: Discussionmentioning
confidence: 99%
“…They may benefit from the pneumococcal vaccine (213), an annual influenza vaccination (213), and routine childhood immunizations, with the exception of live-virus vaccines in immunosuppressed patients. Respiratory syncytial virus can increase the morbidity and mortality of infants and young children with chronic lung diseases, such as chILD syndrome (214); a recent study found significantly increased risk for respiratory syncytial virus hospitalization in children with chILD (215). For this reason, palivizumab is usually considered in significantly compromised infants and young children, even though there have been no related studies to confirm the theoretical benefits of palivizumab.…”
Section: Supportive and Preventive Carementioning
confidence: 99%